Knowledge and practice of vital pulp therapy in young permanent teeth among general dental practitioners in Kerman, Iran - Pishbin, Lida; Sajadi, Fatemeh Sadat; Mahmoudi, Maryam; Shahabinejad, Hassan (International Journal of Dental Research, 2018)
The dental pulp is the living tissue of the tooth and its vitality is essential for long-term tooth survival. The vitality or non-vitality of the pulp as well as the presence or absences of a radicular pathology determine the type of pulp therapy. The knowledge of the dentist is important in selecting and carrying out a proper complete treatment. Therefore, this study was conducted to assess general dental practitioner`s (GDP) knowledge of indication, methods and prognosis of vital pulp therapy (VPT) for young permanent teeth (YPT).Method A total of 160 GDPs from dental clinics and offices in Kerman participated in this descriptive cross-sectional study. Data were collected using an initial questionnaire consisted of 15 items examining the knowledge and practice of indication, methods and prognosis of VPT for YPT among GDPs. The participants were asked to choose from the provided answers.Result of 160 questionnaires 154 were used for final evaluation.The overall obtained average score of the total items of the questionnaire was 4.53 Â± 3.56. There was not any significant correlation between the knowledge of indication, examination, diagnosis, patients selection, effective factors in success of treatment and gender, number of the years since graduation and the university where the degree was obtained for VPT among GDPs. While knowledge of selecting the right materials for pulp-capping was significantly correlated with the number of the years since graduation and the university where the degree was obtained.Conclusion Although GDPs' level of knowledge in regard to VPT is not favorable, the time since graduation and place of education influenced the suitable material selection for pulp capping. Hence, GDPs, who perform pulp therapy , need to keep themselves updated with these procedures.